2020
DOI: 10.1101/2020.06.09.20125831
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimation of effects of contact tracing and mask adoption on COVID-19 transmission in San Francisco: a modeling study

Abstract: The current COVID-19 pandemic has spurred concern about what interventions may be effective at reducing transmission. The city and county of San Francisco imposed a shelter-in-place order in March 2020, followed by use of a contact tracing program and a policy requiring use of cloth face masks. We used statistical estimation and simulation to estimate the effectiveness of these interventions in San Francisco. We estimated that self-isolation and other practices beginning at the time of San Francisco's shelter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…In the United States, as of July 2020, the CDC recommends “that people wear cloth face coverings in public settings when around people outside of their household, especially when other social distancing measures are difficult to maintain” [ 4 ]. Contrary to what some may believe, these cloth masks/face coverings are not designed to protect the mask wearer, but rather, they are intended to protect people within close proximity of the wearer [ 8 ].…”
Section: Types Of Masksmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, as of July 2020, the CDC recommends “that people wear cloth face coverings in public settings when around people outside of their household, especially when other social distancing measures are difficult to maintain” [ 4 ]. Contrary to what some may believe, these cloth masks/face coverings are not designed to protect the mask wearer, but rather, they are intended to protect people within close proximity of the wearer [ 8 ].…”
Section: Types Of Masksmentioning
confidence: 99%
“…A recent study of COVID-19 in San Francisco suggested that the most effective public interventions in reducing virial spread were sheltering in place and contact tracing efforts. However, once shelter in place procedures were lifted, adopting the use of cloth masks by the community was deemed an important and effective means of reducing virus spread [ 8 ]. Chu and colleagues’ recent meta-analysis of 172 observational studies examined the impact of face masks and physical distancing on the transmission of SARS-CoV-2, and reported that face masks (in addition to physical distancing) decreased the transmission of the virus [ 16 ].…”
Section: Types Of Masksmentioning
confidence: 99%
“…As noted by the authors, these findings describe the intention-to-treat effect of face mask mandates at a community or state level, and do not indicate the effect of wearing a face mask in public at an individual level 37 . A number of studies have reported similar positive findings, suggesting that policies mandating face masks are associated with a subsequent decrease in COVID-19 cases 38,39 . However, these policies are rarely introduced in isolation, and it can be difficult to disentangle the effects of multiple measures targeting reduced transmission.…”
Section: Face Masks In the Context Of Covid-19mentioning
confidence: 78%
“…A study from Israel showed that masks are particularly effective when the effective R is close to 1, and can determine whether a low-level epidemic tips into an outbreak or not [22]. In higher transmission settings where the effective R is greater than 1, two studies found that masks are most effective when used in conjunction with a collection of other NPIs [9], [23]. To our knowledge, no studies to date have examined the extent to which face masks can prevent a resurgent outbreak in low-transmission settings.…”
Section: Discussionmentioning
confidence: 99%